Navigating the Maze: A Systematic Review of Empirical Studies on Tax Avoidance and Its Influence Factors - GE, Chao; SU, Wunhong; WONG, Wong Ming (Theoretical and Practical Research in Economic Fields, 2024)
There is a wealth of research on the factors influencing tax avoidance, and it has gradually become a global topic of interest. However, few studies systematically identify which factors influence corporate tax avoidance and how they do so. Many studies on similar topics show significant differences in conclusions across countries. Therefore, a systematic review of the relevant literature on tax avoidance is necessary, as it will help us understand the current state of research and offer insights and directions for future exploration of the reasons behind these discrepancies and the discovery of new factors influencing tax avoidance. This study analyzes 97 empirical studies on tax avoidance, aiming to clarify influencing factors by categorizing themes and summarizing findings. Literature was sourced via Scopus and divided into three sections: Factors influencing tax avoidance in Western countries, factors in China, and future research prospects. Tax avoidance is a complex issue vital to firms’ high-quality development. The study underscores that differing methodologies may lead to varying conclusions, systematizing the literature and drawing comparisons among various perspectives. By enhancing understanding of tax avoidance, the effort provides a foundation for future investigations into practical strategies for firms, contributing to a comprehensive understanding of tax avoidance and emphasizing the importance of a coordinated approach among stakeholders .